Estudo energético da produção de biocombustível a partir do milho - Salla, Diones Assis; Furlaneto, Fernanda De Paiva Badiz; Cabello, Claudio [UNESP]; Kanthack, Ricardo Augusto Dias (Universidade Federal de Santa Maria, 2010)
This research analyzed the energetic consumption of etanol from the corn crops (Zea mays L.). The field surveys were carried out in the Midle Paranapanema River Region, São Paulo state, Brazil, in the period from January to December 2007. The energy consumption on stage of production and industrial processing of grain were evaluated. It was verified that the total energetic cost of the crop production corresponded to 15,633.7MJ ha-1, and the most onerous item was the inputs (77.5%). In the industrial step, the energetic consumption was equivalent to 3,882.2MJ t-1. The operations of hydrolysis, saccharification and treatment of the broth represented 50.2% of the total energetic expenditure. It was also observed an energetic cost of 7.9MJ L-1 in relation to the etanol produced in the main crop production operations, and 11.8MJ L-1 in the industrial processing. The energy balance of crop production and industrialization was of 1.2MJ.

Objetivou-se analisar energeticamente a produção de etanol a partir do milho (Zea mays L.). As pesquisas de campo foram realizadas na região paulista do Médio Paranapanema, São Paulo (SP), no período de janeiro a dezembro de 2007. Avaliou-se o consumo energético referente às fases de produção e processamento industrial do grão. O custo energético total da produção agrícola correspondeu a 15.633,7MJ ha-1, e o item mais oneroso foi o de insumos (77,5%). Nas etapas industriais, o consumo energético foi equivalente a 3.882,2MJ t-1. As operações de hidrólise, sacarificação e tratamento do caldo representaram 50,2% do dispêndio energético total. O custo energético do milho foi de 7,9MJ L-1 nas operações agronômicas de produção e 11,8MJ L-1 nas etapas de processamento industrial. O balanço energético do cultivo e da industrialização foi de 1,2MJ.
Energetic study of ethanol production from the corn crops
Keywords: Zea mays L.; energy balance; renewable energy; environmental sustainability; Zea mays L.; balanço energético; energia renovável; sustentabilidade ambiental